STRATEGI BERTAHAN HIDUP PETANI PENGGARAP DI JORONG SARILAMAK NAGARI SARILAMAK KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Febriani, Dinna; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Survival strategy is a method / strategy undertaken by smallholders in meeting their household needs by utilizing what is in his family. This study aims to mendeskriptifkan profit-sharing system applied owning farmers and sharecroppers and survival strategies sharecroppers in meeting their household needs in Jorong Sarilamak, which sharecropper of the groups working on the fields owned by others because they do not pick the wetland itself so that the results harvest obtained from processing paddy fields belonging to other people will be in for for smallholders and land owners. The data obtained in this study will be used descriptive quantitative method. The technique used in determining the research sample is purposive sampling while the data collection process by using the method of observation and guided interviews. The results obtained from the study, the researchers can say that although peasants not voting fields own land, they are still able to survive and meet the household needs by looking for additional work such as livestock, farm labor, trade, and a handyman. Another way by sharecropper is to involve family members in meeting the needs of their families, and to borrow money from relatives and neighbors when they need urgently needed.Keywords: Farmers Cultivators, Survival Strategies, Sharing System